The Use of Non-Cognitive Diagnostic Assessment on Students' Listening Skills - Agung, Naifah Safa Zafira; Pinesya, Arisca; Nurdiani, Aisyah; Annisa, Salsabila Nur; AR, Silvia; Lubis, Khadijah; Alrefi, Alrefi; Cung, Vinny; Fahmi, Muh (Scidacplus, 2024)
This study aims to describe the results of applying non-cognitive diagnostics to listening skills in class VII.2 students at SMP Negeri 22 Palembang. This research method used descriptive quantitative with data collection techniques in the form of a questionnaire containing 35 questions distributed to a sample of 28 students. In this study, it was found that 46% of students had the medium category in listening skills. Apart from that, the diagnostic results of listening skills showed a mean of 96.18 and a standard deviation (SD) of 10.26. A standard deviation that was smaller than the mean indicated that the distribution of the data variable is small or that there is no large enough gap between the lowest (25%) and highest (29%) ratios.